Unintegrated viral DNA is synthesized in the cytoplasm of avian sarcoma virus-transformed duck cells by viral DNA polymerase. - Varmus, H E (1976)
We have examined the location, structure, and mechanism of synthesis of unintegrated viral DNA present in fully transformed cultures of avian sarcoma virus-infected duck cells. De novo synthesis of the unintegrated forms several weeks after the initial infection was documented by labeling unintegrated DNA in both strands with 5-bromodeoxyuridine. The unintegrated DNA is synthesized in, and probably confined to, the cytoplasm, and it consists of duplexes of short "plus" strands (ca. 0.5 X 10(6) to 1.0 X 10(6) daltons) and "minus" strands the length of a subunit of the viral genome (ca. 2.5 X 10(6) to 3.0 X 10(6) daltons). The structure of the duplex and the mode of incorporation of density label support the hypothesis that the unintegrated DNA is synthesized from an RNA templated by virus-coded DNA polymerase.